1999
DOI: 10.1046/j.1365-2249.1999.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Ro/SS-A-reactive B lymphocytes in salivary glands and peripheral blood of patients with Sjögren's syndrome

Abstract: SUMMARYThe aim of this study was to investigate the production of anti-Ro/SS-A antibodies in labial salivary glands (LSG) and peripheral blood (PB) of Sjögren's syndrome (SS) patients. The ELISPOT method was performed to quantify the frequency of LSG lymphocytes and PB lymphocytes spontaneously secreting anti-Ro/SS-A antibodies. The total number of IgG-, IgA-and IgM-producing cells was also quantified. The bovine Ro 60-kD protein was used as target antigen. Six of six primary SS patients had LSG B cells produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 28 publications
5
59
0
3
Order By: Relevance
“…Quantification of the CD21 ϩ lymphocytes showed that 17% to 20% of the infiltrating cells were CD21 ϩ B cells (not shown), which was in accordance with previous studies (Halse et al, 1999). Our study revealed that CD21 and BAFF colocalized, and we interpret this as the interaction between a BAFFexpressing macrophage and a CD21-expressing B cell as our mAb detects the membrane-bound form of BAFF.…”
Section: Cd21supporting
confidence: 92%
See 1 more Smart Citation
“…Quantification of the CD21 ϩ lymphocytes showed that 17% to 20% of the infiltrating cells were CD21 ϩ B cells (not shown), which was in accordance with previous studies (Halse et al, 1999). Our study revealed that CD21 and BAFF colocalized, and we interpret this as the interaction between a BAFFexpressing macrophage and a CD21-expressing B cell as our mAb detects the membrane-bound form of BAFF.…”
Section: Cd21supporting
confidence: 92%
“…IgG is the predominant isotype expressed by the infiltrating B cells, in contrast to IgA, which dominates in normal salivary glands (Halse et al, 1999). Furthermore, several autoantibodies have been reported in both primary and secondary SS, reflecting both B-cell activation and a loss of immune tolerance in the B-and T-cell compartments (Jonsson et al, 2001b).…”
mentioning
confidence: 99%
“…It is still unknown whether any of the autoantibodies have a pathogenic potential or whether they are all part of a secondary response to salivary glands already damaged by other processes. Anti-SSA/Ro and anti-SSB/La are found in the saliva of SS patients (72), and the B cells that infiltrate the salivary glands contain intracytoplasmic Igs with anti-SSA/Ro and anti-SSB/La activity (39,73,74). In this case, ectopic lymphoid germinal centers that contain Ag-presenting dendritic cells, T cells, and B cells have been found, providing a microenvironment that is conducive to the propagation of the autoimmune response (39).…”
Section: Discussionmentioning
confidence: 99%
“…The chronic inflammation probably leads to the typical functional loss of secretory activity and severe dryness in the mouth (xerostomia) and eyes (keratoconjunctivitis sicca). Additional symptoms of SS represent glandular and extraglandular manifestations, hypergammaglobulinemia, and production of autoantibodies such as anti-Ro/SSA, -La/SSB, and rheumatoid factor commonly detected in serum and saliva as well as in situ in salivary glands (SG) of SS patients (Halse et al, 1999a(Halse et al, , 1999b(Halse et al, , 2000Reichlin et al, 1989;Tengnér et al, 1998). In addition to primary SS (pSS), the disease may occur as secondary SS (sSS) in conjunction with other rheumatic diseases, most frequently rheumatoid arthritis (RA) or systemic lupus erythematosus (SLE) .…”
Section: Broegelmann Research Laboratory (Mo Ks Aib Rj) and Institmentioning
confidence: 99%